A Review on the Challenges of Incorporating Artificial Intelligence (AI) in Teaching - Tenedero, Cynic (Southeast Asian Journal on Open and Distance Learning, 2025)
This paper explains the challenges of incorporating Artificial Intelligence (AI) in teaching in terms of educational resources, personalized learning, motivation. A qualitative library-research design was utilized to study researches published about Artificial Intelligence (AI) from 2018-2025. The challenges of the Artificial Intelligence (AI) integration into educational resources have a significant impact on the teaching practices. Although Artificial Intelligence (AI) provides a positive impact on educational resources such as it can personalize learning and speed up content creation, its implementation must be carefully managed to avoid compromising the human element of education. While AI can improve learning and help keep students motivated, its impact is sometimes reduced by misuse and the difficulty of properly integrating it into teaching. Some students rely too much on AI for assignments, raising concerns about academic honesty. Educators such as teachers and professors must monitor AI-generated content to ensure it meets the academic standards and promotes student engagement.